Dampak Citra Merek dan Pengetahuan Lingkungan terhadap Minat Beli Mobil Hybrid - Winda, Winda; Astaginy, Niar; Ismanto, Ismanto (Innovative: Journal Of Social Science Research, 2025)
This study analyzes the influence of brand image and environmental knowledge on the purchase intention of Toyota Hybrid cars in Kolaka Regency. Using a quantitative method, data was collected through questionnaire distribution. The research sample consisted of 100 respondents, selected using the purposive sampling technique. Data analysis was conducted using SEM-PLS with Smart PLS 4.0. The results show that brand image and environmental knowledge have a positive and significant effect on the purchase intention of Toyota Hybrid cars in Kolaka Regency. Based on these findings, Kalla Toyota Kolaka needs to enhance brand image by highlighting its strengths, such as product quality, after-sales services, and attractive promotions. Additionally, the dealer should build a strong brand identity with a unique and consistent logo, color scheme, and tagline across all communication channels. Regarding environmental concerns, the dealer should increase awareness of pollution issues by implementing emission reduction programs, waste management initiatives, and eco-friendly technology adoption. Furthermore, collaboration with local organizations and communities is essential to enhance environmental awareness and engagement